1998
DOI: 10.1002/hep.510280325
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic preconditioning in rats is defined by a balance of adenosine and xanthine

Abstract: The present work investigates the relationship between adenosine, nitric oxide (NO), and free radicals during ischemic preconditioning in rat liver. For this purpose, we evaluated: 1) the efficacy of different periods of preconditioning; 2) the changes in the concentration of adenine nucleotides during preconditioning; 3) the importance of adenosine and xanthine concentrations in the induction of preconditioning; and 4) the possible effect of xanthine oxidase-derived superoxide anion on NO during preconditioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
93
1
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 17 publications
(31 reference statements)
1
93
1
3
Order By: Relevance
“…It has been similarly reported in the liver that ischemic or heat shock preconditioning exerts a protective effect on hepatic ischemia-reperfusion injury. [10][11][12][13][14][15][16][17][18]24 Although little is known about the molecular basis of the preconditioning, oxidative stress seems to be one of the causes. Peralta et al 15,25 and Yin et al 26 have reported the role of nitric oxide and free radicals during ischemic preconditioning in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been similarly reported in the liver that ischemic or heat shock preconditioning exerts a protective effect on hepatic ischemia-reperfusion injury. [10][11][12][13][14][15][16][17][18]24 Although little is known about the molecular basis of the preconditioning, oxidative stress seems to be one of the causes. Peralta et al 15,25 and Yin et al 26 have reported the role of nitric oxide and free radicals during ischemic preconditioning in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Peralta et al have recently reported that ischemic preconditioning in rat liver is defined by the balance between the tissue concentrations of adenosine and xanthine. 15 They have also suggested that nitric oxide may play the critical role in the ischemic preconditioning. 14,16 In addition, heat-shock protein HSP72 also seems to play an important role for the protection against ischemiareperfusion injury.…”
mentioning
confidence: 99%
“…Preconditioning strategies effective in the laboratory include ischemic preconditioning (IPC), anesthetic preconditioning, hyperthermic or heat-shock preconditioning, and pharmacological preconditioning. [1][2][3][4][5][6][7] In the past decade, serious efforts have commenced to translate some of the robust benefits of preconditioning against ischemia reperfusion (RP) to the clinical arena. Although all of the preconditioning methods offer potential clinical benefits, much of the initial translational effort has focused on IPC, probably due to its extensive and consistently beneficial laboratory experience.…”
mentioning
confidence: 99%
“…This phenomenon, initially studied in the heart by Murry et al in 1986, 13 has been recently described in the liver. 14 The studies on liver ischemic preconditioning, focused mainly on warm ischemia, [14][15][16][17][18][19] suggest that this endogenous mechanism is able to confer protection against liver and lung injuries following hepatic I/R. However, few studies concerning the effectiveness of preconditioning on the I/R injury associated with liver transplantation have been reported, [20][21][22] and these have been mainly centered on the effectiveness of preconditioning in liver grafts submitted for 16 hours or more of cold ischemia.…”
mentioning
confidence: 99%